Comparison of the Mitochondrial Genome Sequences of Six Annulohypoxylon stygium Isolates Suggests Short Fragment Insertions as a Potential Factor Leading to Larger Genomic Size - Deng, Youjin; Hsiang, Tom; Li, Shuxian; Lin, Longji; Wang, Qingfu; Chen, Qinghe; Xie, Baogui; Ming, Ray (Frontiers in Microbiology, 2018)
Mitochondrial DNA (mtDNA) is a core non-nuclear genetic material found in all eukaryotic organisms, the size of which varies extensively in the eumycota, even within species. In this study, mitochondrial genomes of six isolates of Annulohypoxylon stygium (Lév.) were assembled from raw reads from PacBio and Illumina sequencing. The diversity of genomic structures, conserved genes, intergenic regions and introns were analyzed and compared. Genome sizes ranged from 132 kb to 147 kb and contained the same sets of conserved protein-coding, tRNA and rRNA genes and shared the same gene arrangements and orientation. In addition, most intergenic regions were homogeneous and had similar sizes except for the region between cytochrome b (cob) and cytochrome c oxidase I (cox1) genes which ranged from 2,998 bp to 8,039 bp among the six isolates. Sixty-five intron insertion sites and 99 different introns were detected in these genomes. Each genome contained 45 or more introns, which varied in distribution and content. Introns from homologous insertion sites also showed high diversity in size, type and content. Comparison of introns at the same loci showed some complex introns, such as twintrons and ORF-less introns. There were 44 short fragment insertions detected within introns, intergenic regions, or as introns, some of them located at conserved domain regions of homing endonuclease genes. Insertions of short fragments such as small inverted repeats might affect or hinder the movement of introns, and these allowed for intron accumulation in the mitochondrial genomes analyzed, and enlarged their size. This study showed that the evolution of fungal mitochondrial introns is complex, and the results suggest short fragment insertions as a potential factor leading to larger mitochondrial genomes in A. stygium.